When women win, we all win—Call for a gendered global NCD agenda. Issue 12 (25th November 2022) - Ngaruiya, Christine
Abstract: Gender is a social determinant of health, interacting with other factors such as income, education, and housing and affects health care access and health care outcomes. This paper reviews key literature and policies on health disparities and gender disparities within health. It examines noncommunicable disease (NCD) health outcomes through a gender lens and challenges existing prevailing measures of success for NCD outcomes that focus primarily on mortality. Chronic respiratory disease, one of the four leading contributors to NCD mortality, is highlighted as a case study to demonstrate the gender gap. Women have different risk factors and higher morbidity for chronic respiratory disease compared to men but morbidity is shadowed by a penultimate research focus on mortality, which results in less attention to the gap in women's NCD outcomes. This, in turn, affects how resources, programs, and interventions are implemented. It will likely slow progress in reducing overall NCD burden if we do not address risk factors in an equitable fashion. The article closes with recommendations to address these gender gaps in NCD outcomes. At the policy level, increasing representation and inclusion in global public health leadership, prioritizing NCDs among marginalized populations by global health societies and political organizations, aligning the gendered global NCD agenda with other well‐established movements will each catalyze change for gender‐based disparities in global NCDs specifically. Lastly, incorporating gender‐based indicators and targets in major NCD‐related goals and advancing gender‐based NCD research will strengthen the evidence base for women's unique NCD risks and health outcomes.